COMPUTERIZED DESIGN SYSTEM SALES ON BATIK COMPANY MDS USING MICROSOFT VISUAL BASIC 6.0 - Ariyanto Ariyanto; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2005)
This writing describes a computerized system at the company's sales "MDS Batik"which during the process is still done manually, so much the possibility of error andis considered less effective and inefficient. Therefore, the author provides a betteralternative to create a computerized system is a simple batik sales by usingprogramming language Visual Basic 6.0, which will be submitted by the authors toassist with the processing of data through inputing goods production and salesprocess, which will then be automatically saved in a database and will exit the outputdisplay will be received by the customer or buyer as an invoice or receipt and to cometo the view sales reports required by employers tesebut batik cloth.